The Impact of Cultural and Artistic Extracurricular Activities on Student Engagement and Identity in Primary Education in Kosovo - Bunjaku Isufi, Mirlinda (Cultural Arts Research and Development, 2025)
This study examines the impact of cultural and artistic extracurricular activities on student engagement and identity development in primary education in Kosovo, drawing on Bronfenbrenner’s bioecological theory, which highlights the interaction between cultural contexts and student growth. Using a convergent mixed-methods design, 500 participants—250 teachers and 250 parents—were selected through stratified sampling from ten public schools in both urban and rural areas, ensuring balanced representation by gender, teaching experience, and community background. Activities such as music, theater, visual arts, and heritage-based projects were analyzed for their influence on students’ motivation, sense of belonging, and cultural awareness. Quantitative data were gathered via structured questionnaires, while qualitative insights came from interviews with school principals and quality coordinators. Findings revealed a significant link between structured artistic programs and increased participation and emotional engagement. Teachers emphasized creativity and social cohesion as key benefits, while parents underscored the preservation of cultural identity. Folk music, traditional exhibitions, and theatrical performances emerged as the most influential in shaping students’ sense of self. Strong school–family partnerships correlated with higher community involvement and more effective program implementation, though urban–rural disparities persisted in institutional support and resources. The study recommends that national education policies formally integrate the arts into holistic learning, with targeted funding and teacher training to ensure sustainable implementation, particularly in underserved rural schools.